Antibacterial and Toxicity Activities of Indonesian Herbal Medicine Extracts Used for Postpartum Treatment - Wiwit Denny Fitriana; Sri Banun Titi Istiqomah; Devi Anggraini Putri; Taslim Ersam; Adi Setyo Purnomo Purnomo; Nurlatifah Nurlatifah; Sri Fatmawati (Bogor Agricultural University, Indonesia, 2021)
Postpartum treatments have been used by local women in Indonesia for some time now. One commonly used postpartum treatment is the consumption of a traditional herbal medicine called PHM-1 during the first 40 days after childbirth. In addition, a second medicine known as PHM-2 is taken for days 41-80. However, sufficient scientific evidence about the benefits of this postpartum herbal medicine does not exist. In this study, the antibacterial abilities of PHM-1 and PHM-2 therefore was evaluated and showed positive potential for both. Low IC50 values were obtained against pathogenic bacteria such as Escherichia coli, Staphylococcus aureus, Bacillus subtilis, Pseudomonas aeruginosa, Rhodopseudomonas palustris, Ralstonia pickettii, and Staphylococcus epidermidis and compared with chloramphenicol as a positive control. The antibacterial activity of both PHM-1 and PHM-2 against R. pickettii had the highest inhibitory activity as evidenced by the lowest IC50 values of 11.16 and 6.26 μg/ml, respectively. Furthermore, an in vivo acute toxicity test showed that PHM-1 produced a low LD50 value of 3.28 g/kg BW for both of male and female mice. These results support the use of both PHM-1 and PHM-2 as antibacterial treatments for postpartum women.